From Newton's second law "m\\ddot{x}=-kx" where "k" is a spring stiffness, typing "\\omega^2=\\frac{k}{m}" hence "\\omega=\\sqrt\\frac{k}{m}" . From equilibrium "mg=kl" ,where "l=\\frac{1}{4}m" then "k=\\frac{mg}{l}" then "\\omega=\\sqrt\\frac{g}{l}\\approx6.26s^-1"
"x(t)=a\\cos(\\omega t-\\alpha)" ,"v(t)=x_t'=-a\\omega\\sin(\\omega t-\\alpha)"
"x_0(0)=a\\cos\\alpha" ,"v_0(0)=a\\omega\\sin\\alpha" , since "x_0=0.75m" , "v_0=1.25\\frac{m}{s}" hence "a=\\sqrt{x_0^2+\\frac{v_0^2}{\\omega^2}}=0.775" m
"\\frac{v_0}{x_0}=\\frac{a\\omega \\sin\\alpha}{a\\cos\\alpha}=\\omega\\tan\\alpha" ,hence "\\tan\\alpha=\\frac{v_0}{x_0 \\omega}=0.27", hence "\\alpha=\\arctan0.27\\approx15^0\\approx0.083\\pi" then
"x(t)=0.775\\cos(6.26t+0.083)m"
Comments
Leave a comment